Tingkat Pengetahuan Ibu Pascapersalinan tentang Pelaksanaan Senam Postpartum - Muliatul Jannah; Endang Surani; Siti Nurjanah (Jurnal Health Sains, 2022)
Background: During this postpartum period, the postpartum mother will experience many changes in her body, one of which is uterine involution, which is the process of the uterus returning to its normal state as before pregnancy. The reduction in the size of the uterus in the puerperium lasts for approximately 6 weeks, but it can be balanced even faster by doing routine postpartum exercises. Postpartum gymnastics is an exercise that will be able to help return the uterus to a normal state such as before pregnancy after giving birth, so that blood flow can increase and also be smooth, so that this puerperal exercise can affect the uterine shrinkage process. With postpartum exercise, the mother will be given some useful movements to tighten the muscles, especially the abdominal muscles, knees, buttocks, and legs. where these movements are able to help the uterus return to its normal state so that it is faster. During pregnancy and childbirth, a mother will experience many changes in her body, such as the abdominal wall becomes loose, the vaginal opening loosens and the pelvic floor muscles loosen. For this reason, postpartum gymnastics is useful to be able to overcome all the changes that arise after giving birth. Aim : To examine more deeply the knowledge of postpartum mothers on the application of postpartum gymnastics which is in accordance with previous studies by reviewing several studies Method: This review uses several sources including computerized systematic search studies taken over the last five years. The articles obtained in a search are 32 journals, then after doing a deeper study and specified with titles totaling 10 journals with 5 national journals and 5 international journals. The keywords in finding a literature review search were "pregnant women", "postpartum mothers", and "postpartum exercise". Results: After giving birth, a mother will experience many changes physically due to a series of deliveries, the postpartum exercise program itself exists to be able to help post-delivery pregnant women to be able to recover back to normal.